2015
DOI: 10.1007/s40618-015-0326-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral insulin compared to subcutaneous insulin: a systematic review and meta-analysis

Abstract: This systematic review and meta-analysis showed that oral insulin is comparable to SC insulin with regard to glycemic efficacy and safety. However, is necessary to conduct additional studies in which oral insulin administered to large number of patients for long enough periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Oral administration of basal insulin would avoid injections and may also deliver the insulin in a more physiologic manner through absorption through the portal vein [101]. Some studies have shown no significant difference orally and subcutaneously administered insulin in terms of PK, PD, and safety parameters, but larger and longer trials are still needed [102].…”
Section: Future Trends Of Insulinsmentioning
confidence: 99%
“…Oral administration of basal insulin would avoid injections and may also deliver the insulin in a more physiologic manner through absorption through the portal vein [101]. Some studies have shown no significant difference orally and subcutaneously administered insulin in terms of PK, PD, and safety parameters, but larger and longer trials are still needed [102].…”
Section: Future Trends Of Insulinsmentioning
confidence: 99%
“…Seeking innovative strategies to improve treatment compliance for antidiabetic medications might be an effective approach for optimal glycemic control 7–11 . Although subcutaneous insulin injection remains the last choice for patients with type 2 diabetes mellitus (T2DM) and the essential treatment for those with type 1 diabetes mellitus (T1DM), long‐term insulin injection could inevitably increase psychological stress due to pain in the injection site, side effects such as local hypertrophy, skin allergy, and an increased occurrence of hypoglycemia 12,13 . All these effects decreased the acceptance and efficiency of insulin therapy.…”
mentioning
confidence: 99%
“…Oral INS can mimic the natural physiologic route of INS through the portal vein and direct engagement of the liver (Akbari et al., 2016 ). Owing to the first-pass hepatic extraction, 50% of the INS is degraded in the liver (Kanzarkar et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is one of the most common chronic metabolic disease due to lack of insulin (INS) (T1DM) or INS resistance (T2DM) (Sousa et al., 2015 ; Wong et al., 2016 ). Diabetes can be controlled by subcutaneous ( s.c. ) injection with INS (Lopes et al., 2015 ; Akbari et al., 2016 ). Generally, the typical diabetic patients require more than 60,000 injections throughout lives, but the multiple daily injection is with low compliance for patients, such as painful, inconvenient and uncomfortable (Wong et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%